Analisis Pengendalian Biaya Konstruksi Gedung Asrama Dengan Metode Life Cycle Cost - Rini Pebri Utari; Abdul Samad (Universitas Batanghari Jambi, 2021)
Buildings have an important role for human life according to their functions. After the construction process is complete, the building is expected to carry out its functions according to the expected plan age. However, construction with substandard quality building materials causes the building to experience rapid damage resulting in more routine maintenance and high maintenance costs. The object of this research is the Asrema Gedung Putra Polytechnic Bali. One of the appropriate methods in analyzing the economic value of a building starting from planning, implementation and maintenance is to use the Life Cycle Cost Method. From the research results, it is found that four components make up the Life Cycle Cost, namely the initial cost or development cost of Rp. 6,407,566,714 (19%), operational costs Rp. 21,911,035,624 (64%), maintenance and replacement costs Rp. 5,622,402,603 (16%), and the cost for the destruction of Rp. 213,171,382 (1%). And from this research it is also known that the cost of the building component replacement cycle is in accordance with the regulation No. PU. 24 of 2008 so it is expected that the Jembrana Bali Marine and Fisheries Polytechnic Male Dormitory Building can stand for 50 years according to the expected building age.